Sonoporation Enhances Chemotherapeutic Efficacy in Retinoblastoma Cells In Vitro - Lee, Nahyoung G. (Association for Research in Vision and Ophthalmology, Inc., 2011)
PURPOSE. To study the ability of ultrasound (US) and microbubbles (MB) to enhance chemotherapeutic efficacy against retinoblastoma Y79 cells in vitro. METHODS. The experiment was performed in three stages. The authors first compared cell viability of Y79 cells exposed to doxorubicin versus cells exposed to doxorubicin combined with low-intensity, low-frequency US + MB. They then evaluated enhanced cell permeability by studying the intensity of intracellular fluorescence in cells exposed to doxorubicin versus those exposed to doxorubicin with US + MB. Lastly they evaluated the morphologic characteristics of the cells by scanning electron microscopy (SEM) to identify the presence of pores. RESULTS. The Y79 cells exposed to doxorubicin with US + MB showed a significant decrease in cell viability at 72 hours compared with those exposed to doxorubicin alone (P = 0.02). Cells also showed immediate increased permeability to doxorubicin with the addition of US + MB compared with doxorubicin alone, which continued to increase over 60 minutes. SEM did not demonstrate physical pores at the lowest US + MB intensity shown to enhance intracellular doxorubicin fluorescence. CONCLUSIONS. US + MB facilitates the uptake of chemotherapy in retinoblastoma Y79 cells in vitro. This occurs in the absence of visible pores, suggesting a possible secondary mechanism for increased drug delivery. This experiment is the first step toward enhancing chemotherapy with sonoporation in the treatment of intraocular tumors. This technique may lead to more effective chemotherapy treatments with less collateral damage to ocular tissues and may allow reduced systemic dosage and systemic side effects.